Simultaneous electrochemical detection of paraquat and carbofuran using a biodegradable flexible electrode, enhanced with carbon nitride dots and poly(allylamine hydrochloride) via layer-by-layer technique - Freitas, Amanda de Sousa Martinez de; Fré, Lucas Victor Benjamim Vasconcelos; Rodrigues, Jéssica de Souza; Amaro, Stefanny; Barros, Anerise de; Nascimento, Maria Eduarda da Silva; Ferreira, Marystela (Universidade Federal de São Carlos, 2024)
The developing of sensor devices for portable and selective detection remains an emergent technology needed for monitoring water contamination. In this work, we developed a flexible and biodegradable sensor based on the polymer poly(butylene adipate-co-terephthalate) (PBAT) mixed with graphite (g), creating (g-PBAT) for the simultaneous detection of paraquat (PQ) and carbofuran (CBF) pesticides. The g-PBAT was used as an electrode support and was modified with poly(allylamine hydrochloride) and carbon nitride dotes by Layer-by-Layer technique. The sensor’s performance was evaluated through electrochemical methods using cyclic voltammetry, electrochemical impedance spectroscopy, and differential pulse voltammetry. The results demonstrated good reproducibility and repeatability with RSD of 14% and 8.8%, respectively. The stability in terms of current signal peak increased by only 8.5% compared to the initial cycle. The limit of detection (LoD) and limit of quantification (LoQ) were 0.63 μM and 2.10 μM for PQ, respectively, with a sensitivity of 3.69E-5 ± 5.94E-7 A cm−2 M−1, while the CBF had a LoD and LoQ of 7.14 μM and 23.8 μM, respectively, with a sensitivity of 2.51E-7 ± 2.09E-8 A cm−2 M−1. Additionally, the recovery methodology for the real sample showed ranges from 89.3% to 105.0% for PQ, and 92.1% to 105.9% for CBF, indicating that the sensor exhibits good sensitivity and stable RSD, ranging from 4% to 7.5%.
Detecção eletroquímica simultânea de paraquate e carbofurano usando um eletrodo flexível biodegradável, aprimorado com pontos de nitreto de carbono e poli(cloridrato de alilamina) por meio da técnica camada por camada
Keywords: Biodegradable Sensor; Layer-By-Layer; Carbon Nitride Dots; Paraquat and Carbofuran; Sensor Biodegradável; Pontos de Nitreto de Carbono; Paraquat e Carbofurano; CIENCIAS EXATAS E DA TERRA::QUIMICA